Serotyping, MLST, and Core Genome MLST Analysis of Salmonella enterica From Different Sources in China During 2004–2019 - Yan, Shigan; Zhang, Wencheng; Li, Chengyu; Liu, Xu; Zhu, Liping; Chen, Leilei; Yang, Baowei (Frontiers in Microbiology, 2021)
Salmonella enterica (S. enterica) is an important food-borne pathogen, causing food poisoning and human infection and critically threatening food safety and public health. Salmonella typing is essential for bacterial identification, tracing, epidemiological investigation, and monitoring. Serotyping and multilocus sequence typing (MLST) analysis are standard bacterial typing methods despite the low resolution. Core genome MLST (cgMLST) is a high-resolution molecular typing method based on whole genomic sequencing (WGS) for accurate bacterial tracing. We investigated 250 S. enterica isolates from poultry, livestock, food, and human sources in 9 provinces of China from 2004 to 2019 using serotyping, MLST, and cgMLST analysis. All S. enterica isolates were divided into 36 serovars using slide agglutination. The major serovars in order were Enteritidis (31 isolates), Typhimurium (29 isolates), Mbandaka (23 isolates), and Indiana (22 isolates). All strains were assigned into 43 sequence types (STs) by MLST. Among them, ST11 (31 isolates) was the primary STs. Besides, a novel ST named ST8016 was identified, which was different from ST40 by position 317 C→T in dnaN. Furthermore, these 250 isolates were grouped into 185 cgMLST sequence types (cgSTs) by cgMLST. The major cgST was cgST235530 (11 isolates), and only 3 cgSTs contained isolates from human and other sources, indicating a possibility of cross-species infection. Phylogenetic analysis indicated that most of the same serovar strains were putatively homologous except Saintpaul and Derby due to their multi-lineage characteristics. In addition, serovar I 4,[5],12:i:- and Typhimurium isolates have similar genomic relatedness on the phylogenetic tree. In conclusion, we sorted out the phenotyping and genotyping diversity of S. enterica isolates in China during 2004-2019, and clarifies the temporal and spatial distribution characteristics of Salmonella from different host in China in recent 16 years. These results greatly supplements Salmonella strain resources, genetic information and traceability typing data, facilitates the typing, traceability, identification and genetic evolution analysis of Salmonella, and therefore improve the level of analysis, monitoring and controlling of foodborne microorganisms in China.